Impact of integrated care coordination on pediatric asthma hospital presentations - Homaira, Nusrat; Dickins, Emma; Hodgson, Stephanie; Chan, Mei; Wales, Sandra; Gray, Melinda; Donnelly, Sarah; Burns, Christine; Owens, Louisa; Plaister, Michael; Flynn, Anthony; Andresen, Jennifer; et al. (Frontiers in Pediatrics, 2022)
Introduction Frequent asthma attacks in children result in unscheduled hospital presentations. Patient centered care coordination can reduce asthma hospital presentations. In 2016, The Sydney Children's Hospitals Network launched the Asthma Follow up Integrated Care Initiative with the aim to reduce pediatric asthma emergency department (ED) presentations by 50% through developing and testing an integrated model of care led by care coordinators (CCs). Methods The integrated model of care was developed by a multidisciplinary team at Sydney Children's Hospital Randwick (SCH,R) and implemented in two phases: Phase I and Phase II. Children aged 2–16 years who presented ≥4 times to the ED of the SCH,R in the preceding 12 months were enrolled in Phase I and those who had ≥4 ED presentations and ≥1 hospital admissions with asthma attack were enrolled in Phase II. Phase I included a suite of interventions delivered by CCs including encouraging parents/carers to schedule follow-up visits with GP post-discharge, ensuring parents/carers are provided with standard asthma resource pack, offering referrals to asthma education sessions, sending a letter to the child's GP advising of the child's recent hospital presentation and coordinating asthma education webinar for GPs. In addition, in Phase II CCs sent text messages to parents/carers reminding them to follow-up with the child's GP. We compared the change in ED visits and hospital admissions at baseline (6 months pre-enrolment) and at 6-and 12-months post-enrolment in the program. Results During December 2016-January 2021, 160 children (99 in Phase I and 61 in Phase II) were enrolled. Compared to baseline at 6- and 12-months post-enrolment, the proportion of children requiring ≥1 asthma ED presentations reduced by 43 and 61% in Phase I and 41 and 66% in Phase II. Similarly, the proportion of children requiring ≥1 asthma hospital admissions at 6- and 12-months post-enrolment reduced by 40 and 47% in Phase I and 62 and 69% in Phase II. Conclusion Our results support that care coordinator led integrated model of asthma care which enables integration of acute and primary care services and provides families with asthma resources and education can reduce asthma hospital presentations in children.